Improving dexamethasone drug loading and efficacy in treating rheumatoid arthritis via liposome: Focusing on inflammation and molecular mechanisms - Mohammad Yasin Zamanian; Hamidreza Zafari; Maria K. Osminina; Alla A. Skakodub; Raed Fanoukh Aboqader Al‐Aouadi; Maryam Golmohammadi; Nikta Nikbakht; Iman Fatemi (Animal Models and Experimental Medicine)
Abstract Rheumatoid arthritis (RA) is a chronic autoimmune disease that affects approximately 0.46% of the global population. Conventional therapeutics for RA, including disease‐modifying antirheumatic drugs (DMARDs), nonsteroidal anti‐inflammatory drugs (NSAIDs), and corticosteroids, frequently result in unintended adverse effects. Dexamethasone (DEX) is a potent glucocorticoid used to treat RA due to its anti‐inflammatory and immunosuppressive properties. Liposomal delivery of DEX, particularly when liposomes are surface‐modified with targeting ligands like peptides or sialic acid, can improve drug efficacy by enhancing its distribution to inflamed joints and minimizing toxicity. This study investigates the potential of liposomal drug delivery systems to enhance the efficacy and targeting of DEX in the treatment of RA. Results from various studies demonstrate that liposomal DEX significantly inhibits arthritis progression in animal models, reduces joint inflammation and damage, and alleviates cartilage destruction compared to free DEX. The liposomal formulation also shows better hemocompatibility, fewer adverse effects on body weight and immune organ index, and a longer circulation time with higher bioavailability. The anti‐inflammatory mechanism is associated with the downregulation of pro‐inflammatory cytokines like tumor necrosis factor‐α (TNF‐α) and B‐cell–activating factor (BAFF), which are key players in the pathogenesis of RA. Additionally, liposomal DEX can induce the expression of anti‐inflammatory cytokines like interleukin‐10 (IL‐10), which has significant anti‐inflammatory and immunoregulatory properties. The findings suggest that liposomal DEX represents a promising candidate for effective and safe RA therapy, with the potential to improve the management of this debilitating disease by providing targeted delivery and sustained release of the drug.